Three essays on the economics of restoring degraded land: from global to local - Verdone, Michael, author; Seidl, Andrew, advisor; Frasier, Marshall, advisor; Brown, Thomas, committee member; Brown, Cynthia, committee member (Colorado State University. Libraries, 2016)
To view the abstract, please see the full text of the document.
Keywords: dynamic programming; forest restoration; ecosystem services; conservation agriculture; land degradation; Monte Carlo simulation